2019
DOI: 10.1126/sciadv.aaw9051
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic stabilization of DC and DC precursor classical activation by TNFα contributes to protective T cell polarization

Abstract: Epigenetic modifications play critical roles in inducing long-lasting immunological memory in innate immune cells, termed trained immunity. Whether similar epigenetic mechanisms regulate dendtritic cell (DC) function to orchestrate development of adaptive immunity remains unknown. We report that DCs matured with IFNγ and TNFα or matured in the lungs during invasive fungal infection with endogenous TNFα acquired a stable TNFα-dependent DC1 program, rendering them resistant to both antigen- and cytokine-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 76 publications
2
26
0
Order By: Relevance
“…This is due, at least in part, to a limited understanding of how dysregulated CNS inflammation causes neurological pathology during CM, as well as a lack of reliable biomarkers to separate patients with CM with inadequate versus exaggerated neuroinflammatory responses (11,13,15). The vast majority of mechanistic studies on host defense in cryptococcal infections use murine pulmonary infection models, in which T helper 1 (T H 1)-polarized T cell-mediated responses were shown to be protective and to limit disease pathology (16)(17)(18)(19)(20)(21). The signature T H 1 cytokines, interferon- (IFN-) and tumor necrosis factor- (TNF-), activate fungicidal responses in pulmonary effector phagocytes (monocytes, macrophages, and monocyte-derived dendritic cells), marked by the production of nitric oxide (NO) via inducible NO synthase (iNOS) (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…This is due, at least in part, to a limited understanding of how dysregulated CNS inflammation causes neurological pathology during CM, as well as a lack of reliable biomarkers to separate patients with CM with inadequate versus exaggerated neuroinflammatory responses (11,13,15). The vast majority of mechanistic studies on host defense in cryptococcal infections use murine pulmonary infection models, in which T helper 1 (T H 1)-polarized T cell-mediated responses were shown to be protective and to limit disease pathology (16)(17)(18)(19)(20)(21). The signature T H 1 cytokines, interferon- (IFN-) and tumor necrosis factor- (TNF-), activate fungicidal responses in pulmonary effector phagocytes (monocytes, macrophages, and monocyte-derived dendritic cells), marked by the production of nitric oxide (NO) via inducible NO synthase (iNOS) (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, results of Menachery et al (2018) revealed a possible association of H3K27me3 global methylation with downregulation of ISG and DNA methylation of antigen presentation gene upon MERS-CoV and H5N1VN1203 [ 66 ]. The possible association of TNF-α and H3K4me3 in the induction of trained innate immunity in monocytes and DC1 antigen presentation and TH1/TH17 immunity upon infection has been described previously [ 67 , 69 ]. Mechanistically, it was observed that an increase in either TNF-α or IFN-γ is sufficient to induce the MLL1 activity which stimulates H3K4 methylation and is required for DC stabilization [ 67 ].…”
Section: Epigenetic Approach Of Coronavirus Immune Evasionmentioning
confidence: 95%
“…HDAC mediates the regulation of non-histone proteins involved in mechanisms crucial for cellular functions like DNA repair, replication, P53 signaling, HIF-1α, STAT3 or p65. HDAC macrophages display a pro-inflammatory function by producing pro-inflammatory cytokines like TNF-α, MCP-1, IL-1α, IL-1β and IFN-γ and are a potential target for HDAC inhibitors [ 69 ]. The role of HDAC2 in modulating the NF-κB activity plays a significant role in the immune evasion strategy of SARS-CoV-2.…”
Section: Epigenetic Approach Of Coronavirus Immune Evasionmentioning
confidence: 99%
“…Trained monocytes and macrophages were described essentially by their ability to more efficiently produce cytokines, especially IL-6 and TNFa, upon exposure to unrelated stimuli (29,(34)(35)(36)(37). Other cells from the myeloid lineage, such as DCs (29,38,39) and even neutrophils (40)(41)(42)(43), despite their very short life span, were recently reported to display enhanced innate functions long after the initial stimulation. A burgeoning diversity of neutrophil phenotypes and functionalities are being uncovered, with their capacity to act as APCs a current focus of investigation (44).…”
Section: Trainable Cellsmentioning
confidence: 99%